Analysis Of Organizational Commitment, Work Performance And Personality On The Performance Of PT Kawasan Industri Medan Industry (KIM) - Suci Mentari; Wilchan Robain; Eli Delfi Yanti; Halimatussa'diah (International Journal of Management, Economic and Accounting, 2025)
The research analysis aims to analyze organizational commitment, work performance and personality to the performance of employees of PT Kawasan Industri Medan (KIM). The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 89 respondents. Primary data collection uses questionnaires. The results of the study show that the test results for the organizational commitment variable show a t-value of 2.650 > a t-table of 1.98 with a significant value of 0.000 < 0.05, then the H1 hypothesis is accepted and H0 is rejected. The test results for the work performance variable showed a calculated t-value of 6.690 > a ttable of 1.98 with a significant value of 0.026< 0.05, then the H2 hypothesis was accepted and H0 was rejected. The test results for personality variables showed a calculated t-value of 9.260 > a t-table of 1.98 with a significant value of 0.014< 0.05, then the H3 hypothesis was accepted and H0 was rejected. The results of the test were simultaneous with a value of F calculated as 549.751 which was greater than 2.76 and a significant value of 0.000 was less than 0.05 so that it could be concluded that hypothesis 4 was accepted and hypothesis 0 was rejected.